It all begins with jelly beans - Weetman, Nova (Margaret K. McElderry Books, 2022)
When they are selected to read speeches at their elementary school graduation, an unlikely friendship develops between two sixth-graders, one popular and one a misfit, who are facing family problems and health issues.